10.1001/TESTjama.2012.6380 (CrossRef Listing of Deleted DOIs, 2000)
Importance The UK relies heavily on internationally trained physicians and nurses. The 2016 UK European Union (EU) membership referendum (Brexit referendum) introduced uncertainty regarding future migration policy, with unclear implications for health care workforce supply and National Health Service (NHS) staffing. Objective To evaluate changes in immigration of internationally trained physicians and nurses to the UK after the Brexit referendum and to assess associated changes in NHS vacancies. Design, setting, and participants A controlled interrupted time-series study was conducted to assess changes in physician and nurse immigration to the UK after the 2016 Brexit referendum, using annual data for 2008 through 2019 from the Organization for Economic Cooperation and Development (OECD) with 32 high-income OECD countries as the control group; an interrupted time-series study was undertaken to estimate changes in NHS England vacancies due to the Brexit referendum, using monthly vacancy data from April 2015 to December 2019. Data were analyzed from January 2024 to June 2025. Exposures 2016 Brexit referendum. Main outcomes and measures Annual inflow of EU-origin, non-EU-origin, and total physicians and nurses to the UK; monthly NHS England physician and nursing vacancies. Results The analysis included 418 962 physicians and 358 122 nurses who emigrated to an OECD country from 2008 to 2019. In 2016, the Brexit referendum was associated with immediate reductions of 825 EU physicians (95% CI, -983 to -668) and 2771 EU nurses (95% CI, -2952 to -2590) relative to prereferendum trends. Non-EU immigration also fell in 2016 (-416 physicians [95% CI, -746 to -83]; -2912 nurses [95% CI, -3463 to -2362]) but increased significantly thereafter from 2017 to 2019 (added 3110 physicians per year [95% CI, 2745 to 3474] and 1437 nurses [95% CI, 1036 to 1838]). Overall, total physician inflow rose, while total nurse inflow declined. NHS England physician vacancies increased by 383 posts (95% CI, 88 to 679) immediately after the referendum; nursing vacancies showed no significant changes. Conclusions and relevance In this cross-sectional study, the Brexit referendum's policy uncertainty produced a sustained decline in EU-origin health care worker immigration, partially offset by recruitment from non-EU countries. This substitution did not prevent increases in physician vacancies and persistent nursing shortfalls, underscoring the sensitivity of health workforce supply to migration policy. Policymakers considering similar restrictions should account for anticipatory effects, substitution dynamics, and potential consequences for global health equity.